The Oksywie Culture on the Right-Bank Lower Vistula - Teska, Milena (Archaeologia Lituana, 2015)
The investigations of sites of the earliest prehistory are not distinguished by consistency and geographical evenness in Lithuania. The majority of the excavated Stone Age sites and settlements are located in the South Lithuania where a surface flint raw material is abundant. Other concentration place of the Stone Age sites is the biggest rivers’ (Nemunas, Neris, Šventoji) valleys in the Middle Lithuanian. Also the Stone Age sites are abundant on the banks of some larger (Biržulis, Kretuonas) and smaller (Jara) lakes of the country. But till now the regions, which are at some distance from the main inland arterial waters, are not investigated by researchers, especially the hilly morainic territories of the glacial origin. Kalviai Lake (Kaišiadorys dist., Kruonis county) is located on the west side of Aukštadvaris hilly morainic territory (a part of Dzūkai Highland) within the area of marginal moraines from the Late Weichsel Glaciation (the South Lithuania phase). The large Lake glaciodepression was partly reformed by the fluvioglacial processes; therefore its banks are rather steep and cut out by large amount of ravines and gullies. The till-clayey background of the glaciodepression is covered in many places by gravelly-sandy sediments. Nowadays, Kalviai Lake occupies an area of c. 180.8 ha: about 2.8 km in length and 0.5–1.4 km in width with large bay in the southeastern part. In the past the Lake was much bigger (about 5.7 km in length) with the large bays at the west and east ends, but the deepening erosion of the outlet river Lapainia drained the Lake gradually and the bays became boggy. Kalviai Lake is formed in a tunnel valley, but today the Lake depth is not big (c. 7–8 m) because greater part of the Lake depression is filled with sediments (Fig. 1). During the reconnaissance investigation, prepared in 1995 by A. Girininkas and in 1994–2010 by E. Šatavičius, 13 Stone Age sites and settlements from the Final Palaeolithic to the Neolithic periods were found on the banks of Kalviai Lake (Fig. 2). The rare earliest sites (Kalviai 1, 2, 4) which are dated to the Final Palaeolithic, situated mostly on the south-southeast banks of the Lake at higher level – about 6–17 m above the nowadays Lake water level. The Mesolithic sites are more abundant and discovered on the southern-southeastern (Kalviai 1, 2, 3, 4, 5) and on the western (Šventininkai 1, 2, Vilūnai 1, 2, 3) banks of the Lake. These sites are situated mostly at lower level of terraces, close to the water. In certain cases the lowest part of their cultural horizons are covered by peats. The similar distribution of the sites is characteristic to the Neolithic period, too. Such sites were found on the southern-southeastern (Kalviai 3, 5), western (Vilūnai 1, 2) and northern (Būtkiemis 1, 2) banks of the Lake on lower terraces (1–4 m high). In some cases they situated in long peninsulas and islands. Kalviai 1 site is situated on the south bank of Lake Kalviai, about 1.49 km to the southeast of Lapainia River where it falls into the lake, and about 0.1 km to the southwest of the Lake bank. In respect to geomorphology, it is situated on the upper (Habs 101–105.5 m) terrace of the Lake, but a little away from its edge, in a shallow hollow (Fig. 3). From the northeast–southeast sides’ the site was bounded by the Lake bay. Kalviai 1 site was found during a field evaluation in 1995. On the basis of the incidence of surface artefacts, it is possible to state that the site preliminarily occupies an area of around 130 Ч 100 m. Broad-scale excavations were conducted at the site during 1999–2000. During two excavation seasons, the present author himself excavated a total of 80 m2 in the central part of the site. The excavations were made using adjoining rectangular trenches. All of the soil was removed using trowels in separate 2–4 cm thick layers. During the excavation, the following stratigraphy was observed at the site: on top was sod and a dark grey, 20– 60 cm thick layer of soil (which had been destroyed through ploughing); below this lay was a sterile yellowish-brownish sandy gravel (Fig. 4–5). About 850 flint finds were found in the site during the excavation (Fig. 5). The majority of them did not lie in their original position, but in the layer of grey soil that had been destroyed by ploughing. Only 12 of them lay in the cultural horizon. About 65% of the finds were covered by a thick white patina. The rest part of the finds was covered by a thin bluish-white patina or they lack of it. About 11% of all of the flint finds had been in a fire. Besides many flint finds had been spoiled by long-time ploughing: fragmented into several parts, with “retouched” edges and scratched surfaces. High quality grey flint raw materials (Baltic erratic flint), which are found in abundance in South Lithuania and in the larger river valleys, were used for knapping mostly. The absolute majority of the finds (about 99% of all of the finds) found in the trench consist of debitage and blanks from primary and secondary flint reduction stages, i.e. flakes and blades. Direct blow and soft percussion technique was used mostly. 2 cores (double platform and single platform) and one flint tool (burin on truncation) were discovered during the excavations. Besides, 6 double platform cores, 2 burins (dihedral and on truncation), an axe as well as one hundred of flakes and blades were found on the site surface (Fig. 6; 7).It could be noted that the site was non-simultaneous and consisted of several separate locus of different times, the limits of which were deleted and finds mixed by long time ploughing. According to flint finds technological-typological criteria the assemblage could be separate into two different complexes. The flint finds of the oldest complex are covered with deeper bluish-whitish patina and belonged to Ahrensburgian or Swiderian culture (Younger Dryas period). Another one with thin bluish patina or without it is belonged to an unknown culture of the first half of the Mesolithic period. The carried out investigations clearly indicate that hilly morainic territories with lakes of various size are abundant in the Stone Age sites. Such one micro-region is investigated by author in the East Lithuania close to Žalesas Lake (Verbiškės-Miškiniai sites).